Finding New Ways of Creating Value: A Case Study of Servitization in Construction: One company's journey toward servitization illustrates how systems integrators can capture value through long-term customer relationships. Issue 3 (3rd May 2016) - Robinson, William; Chan, Paul; Lau, Thomas
OVERVIEW: Using activity theory as a framework, this paper explores how organizational changes enabled a multinational construction company to transform its business model in pursuit of servitization. Following one firm's journey toward servitization over a 33-month period, the study demonstrates how the mobilization of new resources across the supply chain, the development of new products, and the creation of new service offerings enabled the organization to create and capture value in new ways. Given the lack of research on systems integrators and servitization, the case offers some important insights. It suggests that systems integrators must carefully consider their position within their existing value chain as they shift toward servitized business models and then constantly coordinate internal and external activities as they move forward. For instance, Laing O'Rourke developed new offerings by exploiting data from across the supply chain and integrating design and manufacturing processes to create possibilities to capture value through long-term customer relationships. The use of activity theory as a frame for the analysis offers a new way of examining how these firms move toward servitization and what barriers they face.